Inventory models with stock-dependent demand: a comprehensive review and its linkage with waste management. (2018) - Sharma, Neeta; Vrat, Prem
This paper presents a review of the advances in stock-dependent demand inventory literature for the last three decades. The available relevant models have been classified into a number of categories and their principal features have been discussed in brief to bring out more pertinent information regarding model development. An extensive analysis of the literature is presented to identify the future research scope and the factors which are responsible for the poor applicability of these models. Moreover, a very important and missing link between the stock-dependent demand phenomenon and waste has been recognised as a potential field for exploration in materials management as well as in our day-to-day consumption pattern. It has been emphasised that many socio-economic problems which have a root cause in wasteful resource consumption can be solved by incorporating the phenomenon in our waste management practices.